Visualization and Message Design Concepts of Presenting Statistical Data through Videos to Improve Understanding - Muhammad Lukman Haris Firmansah (International Journal of Multidisciplinary Sciences and Arts, 2022)
Learning statistics generally still presented in the form of stories in the books. This study aims to determine the visualization of the basic concepts of presenting statistical data using video. video designs stories into real stories experienced by students so that fact objectivity is created. it aims to make the messages in the story match the experiences experienced by students. this creating recaling knowledge and creating understanding. The research method used in this research is qualitative research with the phenomenological type, where the video is visually used to present messages, namely the concept of presenting data in tables and diagrams. The presentation technique in the video is in the form of a message demonstration that contains facts, concepts, procedures and principles. As for the data analysis used later, namely the observation data, interviews and documentation after using the video by means of data triangulasi. The research of this study were to compare the observation data, interviews and documentation in the form of student understanding data. Based on the observation data, it shows that students pay attention to the video and can explain the story again in the video. interview data shows and answers many type of data and its presentation. documentation data in the form of activity data in class at the second meeting compared to data at the first meeting without using video. Observations, interviews and the results obtained that observations with the aim of knowing whether students understand the sequence in the story is worth 74%, remembering the presentation data 86%, understanding the explanation of data in tables and diagrams 84%, explaining and explaining problems when the video is repeated 75%. This data was obtained when making observations and asking students when they were shown a video.